Nilai pendidikan Moral Dalam Novel Harga Sebuah Percaya Karya Tete Liye - Pandiangan, Analisa Januati; Shomary, Sudirman (UIR Press, 2024)
The value of moral education is a value related to a responsible human person. The value of moral education aims to appreciate and respect humans as humans and treating humans as humans is the human obligation of every human being. Darmadi (2012: 51). Problems in this research: 1) What are the values of moral education and their relationship to the educational realm of Bloom's Taxonomy in the aspects of responsibility, conscience and obligation contained in the novel Harga a Confidence by Tere Liye. The theories used in this research are Bertens (2001), Kusniati (2012), Moleong (2018). The method the author uses is a descriptive method using content analysis techniques. The data collection technique was carried out using hermeneutic techniques. The results of this research show that the value of moral education in the novel Harga a Confidence by Tere Liye which is related to aspects of responsibility contains 15 data, for example;